2017
DOI: 10.1363/psrh.12044
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Knowledge and Experiences Among U.S. Servicewomen: A Qualitative Study

Abstract: Policy recommendations to better meet the needs of servicewomen include wider dissemination of the military's abortion policy, establishing abortion referral and support guidelines, and improving confidentiality in military health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In some circumstances, bene ciaries were eligible for reimbursement for travel for the procedures due to the care not being available in network. (20)(21)(22) Our ndings show that in our two comparator states (Texas and Virginia), the immediate implementation of abortion access restrictions was associated with higher rates of vasectomy utilization post Dobbs decision. This nding has been replicated in at least one other study; however no direct analysis on the effect of restrictions by differing gestational age, or other factors on the rate of vasectomy post Dobbs has been published to date.…”
Section: Discussionmentioning
confidence: 65%
“…In some circumstances, bene ciaries were eligible for reimbursement for travel for the procedures due to the care not being available in network. (20)(21)(22) Our ndings show that in our two comparator states (Texas and Virginia), the immediate implementation of abortion access restrictions was associated with higher rates of vasectomy utilization post Dobbs decision. This nding has been replicated in at least one other study; however no direct analysis on the effect of restrictions by differing gestational age, or other factors on the rate of vasectomy post Dobbs has been published to date.…”
Section: Discussionmentioning
confidence: 65%
“…89 Because of the societal stigma that surrounds abortion, women go to great lengths to maintain the privacy of their abortion in both legally restrictive and permissive settings. 19,90 Healthcare facilities should ensure their policies and staff maintain the privacy and con dentiality of all patients. Women undergoing abortion care have the right to be a rmed as moral decision-makers, determine their involvement in their care, and receive care that is provided discreetly and without judgment.…”
Section: Individual and Societal Factorsmentioning
confidence: 99%
“…1 3 Because pregnant servicemembers cannot remain in certain military positions or roles, they lose work time during and after pregnancy, and must also be evacuated if deployed and returned to their home station. 14 Prior research has found concerns among servicemembers that pregnancy and associated stigmas, lost work time, and deployment disruptions could harm their careers, [15][16][17][18] despite official guidance that pregnancy will not be the basis for downgrading marks or adverse career impacts. 12 For servicemembers seeking to terminate a pregnancy, federal law only allows abortion provision and TRICARE insurance coverage in cases of rape, incest, and life endangerment of the pregnant person.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found numerous barriers to servicemembers seeking abortion care on their own, including legal, logistical, and financial barriers, concerns about confidentiality, and fear of negative career impacts. [15][16][17] In the civilian population, the percentage of unintended pregnancies that resulted in abortion was 42% in 2011. 11 There are no published data on the prevalence of abortion among US servicemembers with unintended pregnancies.…”
Section: Introductionmentioning
confidence: 99%